Desire to have children among people living with HIV in post-conflict Northern Uganda : a mixed methods study - Nattabi, Barbara (Curtin University, 2012)
Millions of people continue to contract the HIV virus every year, includingthousands of children in Sub-Saharan Africa who mainly contract HIV throughmother-to-child transmission (MTCT). Several factors are responsible for thiscontinued transmission and include lack of access to HIV testing for at-riskpopulations and limited treatment services for people living with HIV (PLHIV). Inaddition, many HIV-infected children are born to PLHIV who desire to have children despite the risk of HIV transmission to their infants.Informed by a pragmatic paradigm and using the Social Ecological Framework, this study explored the factors that influence desire to have children among PLHIV in Northern Uganda, a post-conflict region of high HIV prevalence. A mixed-methods design constituting a survey and semi-structured interviews was selected for this study. Between February and May 2009, 476 PLHIV from three HIV clinics within Gulu District were recruited to take part in the study. A 121-item questionnaire was administered to each respondent to collect socio-demographic information, sexual and reproductive history, family planning knowledge and use, fertility desires and intentions, and experiences of stigma. In the qualitative arm of the study, interviewers explored with 26 participants using a semi-structured guide their desire to have children, experiences of family planning and stigma in order to gain a deeper understanding of the desire to have children among PLHIV, the use of family planning methods and detailed understanding of the processes of stigmatisation of PLHIV in Northern Uganda.This study found a high level of desire to have more children among PLHIV in Gulu District. Forty three percent of the respondents desired more children, including 54.2% of male respondents and 31.7% of female respondents (p<.001). Male sex, being single, and spouses’ desire to have children were associated with an increased desire to have children. The factors influencing PLHIV’s desire to have children included availability of highly active antiretroviral therapy (HAART), and prevention of mother-to-child transmission (PMTCT) programs, spouse, family and society expectations, the desire to have heirs, and cultural influences. Most of the PLHIV were concerned about MTCT, some had personal health concerns and others were concerned about their children’s futures.This study also found a high level of knowledge of family planning methods (96%), but very low use of contraception at 38%. A significantly higher proportion of males (52%) than females (25%) were using contraception. Factors associated with the use of contraception were having ever gone to school, discussion of family planning with a health worker or with one’s spouse, not attending the Catholic-based clinic and spouses’ non-desire for children. The qualitative data revealed six major factors influencing contraception use, including personal and structural barriers to contraceptive use, perceptions of family planning, and decision-making, covert use of family planning methods and targeting of women for family planning services.This study found that several factors were associated with the stigmatisation of PLHIV in Northern Uganda including being female, being on HAART, being older and having a diagnosis of HIV for longer. Using the Conceptual Framework of HIV/AIDS Stigma, this study further delineated the process of stigmatisation which included the factors that trigger stigma, stigma behaviours, outcomes of the stigmatisation process and the agents involved in stigmatisation of PLHIV. The latter included family, communities and the health system all of which can mitigate and/or enhance stigmatisation of PLHIV and lead to increased or decreased desire to have children among PLHIV.In conclusion, the high level of desire to have children among PLHIV is understandable given the multi-level and multi-factor influences including factors at the individual level (sex, marital status, personal health concerns, concerns about the children’s future and their potential infection, the desire to have heirs and fulfil family and societal obligations), interpersonal level (gender roles, interactions with spouses, family members and health workers), community level (community stigma and cultural norms) and structural levels (availability of HAART and PMTCT programs). Other superstructural factors influencing the desire to have children include the high levels of poverty, and gender inequality. Health workers and program managers at a local, national and international level must work with PLHIV for better health outcomes with provision of counselling, family planning services and extension of HAART and PMTCT programs to both help reduce the incidence of HIV among children and meet the reproductive desires of PLHIV.